Pemberdayaan Murid SDN Lamatou melalui Pendampingan Belajar di Rumah untuk Meningkatkan Motivasi Belajar Masa Covid-19 - Ilyas, Ilyas; Baluk, Anastasia Boda; Liu, An Nisaa Al Mu’min (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2022)
Lamatou State Elementary School, located in Painapang Village, Lewolema District, East Flores Regency, East Nusa Tenggara Province is one of the schools affected by Covid-19. During the Covid-19 period, this school dismiss its students and carried out online learning. In addition to online learning, teachers also visit students' homes to provide assistance for students who do haven't Android phones or students who do have limited funds to buy data package credits. Teaching mentoring activities at students' homes are carried out for one month in order to increase the motivation to learn of SDN Lamatou students during covid-19. The results of the one-month activity show that SDN Lamatou students are motivated and hope to continue studying at home through mentoring. This can be seen from the responses of the students through the questionnaires distributed after the mentoring.